1997
DOI: 10.1021/bk-1997-0664.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Trichloroethylene with Hybrid Poplars

Abstract: We tested the ability of hybrid poplar to absorb trichloroethylene (TCE) from groundwater. Initial studies used axenic tumor cultures of H11 -11 grown in the presence of 14 C-TCE. These cells metabolized the TCE to produce trichloroethanol, di-and trichloroacetic acid. Some of the TCE was incorporated into insoluble, non-extractable cell residue, and small amounts were mineralized to 14 C-CO 2 . Rooted poplar cuttings grown in PVC pipes produced the same metabolites when exposed to TCE. Mass balance studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 6 publications
1
37
0
1
Order By: Relevance
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 88%
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 88%
“…The use of larger plants that are not currently classified as hyperaccumulators can compensate for somewhat lower accumulation factors in aboveground organs with greater biomass production and high transpiration rates. Poplar, which has emerged as a model system for genomic approaches to wood formation and tree physiology (Sterky et al, 1998;Taylor, 2002;Kohler et al, 2003), also is a good candidate for phytoremediation purposes (Gordon et al, 1998;Rugh et al, 1998;Pilon-Smits and Pilon, 2002;Stanton et al, 2002;Di Baccio et al, 2003). Thus, an ideal plant for phytoremediation purposes would combine high biomass production and superior capacity for pollutant accumulation and tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Others have demonstrated similar uptake rates. For example, Gordon et al (1997) reported that a stand of 5 year old poplars could cause a 140 cm/year draw-down in the water table when grown at a density of 1,750 trees/ha in the warm, arid conditions of eastern Washington state.…”
Section: Wsrc-sti-mentioning
confidence: 99%